Evaluasi Pola Pengangkutan Sampah Zona III (Kecamatan Rumbai Dan Kecamatan Rumbai Barat) - Silvi Nora; Jecky Asmura; Elvi Yenie (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Waste is the residue of human activities that form of solid waste. Waste needs to be managed to avoid having a negative impact. One effort to manage a waste is to make the transportation of waste. The purpose of this research is to evaluate the transport of waste regarding the transport of waste in Zone III (Rumbai and West Rumbai District). Result of this research suggest that longer the distance a route takes, the greater the time it takes, it can be seen from the amount of time that TP 57 uses to drive longest. TP 57 have the longest route 62,95 Km. The exciting of waste transportation system in Zone III uses a direct pattern and manual SCS. The averaget total amount of time that is used to transport garbage per rotation is 5,110 hours/rotation, and the average of ritaion is 2 ritations per day. Calculating data indicate that waste hauling is ineffective and unproductive Productivity of waste hauling activities can be seen at off-route value. Average score off route That value falls below the range of productive waste hauling values. 0,09.Keywords: Waste Transportation, Waste transportation route, Waste transportation disances, Waste transportation time